To solve the system of equations:
7x + 3y = -25 (Equation 1)
-7x + 9y = -47 (Equation 2)
We can solve by elimination or substitution method. I will use the elimination method here:
Multiply Equation 1 by -7, and Equation 2 by 7 to eliminate the x term:
-7(7x + 3y) = -7(-25)
7(-7x + 9y) = 7(-47)
Simplify:
-49x - 21y = 175
-49x + 63y = -329
Now subtract the second equation from the first equation:
(-49x - 21y) - (-49x + 63y) = 175 - (-329)
-49x - 21y + 49x - 63y = 175 + 329
Simplify:
-84y = 504
y = 504 / -84
y = -6
Substitute the value of y = -6 back into Equation 1:
7x + 3(-6) = -25
7x - 18 = -25
7x = -25 + 18
7x = -7
x = -7 / 7
x = -1
The solution to the system of equations is x = -1 and y = -6.
Question%0D%0ASolve the system of equations.%0D%0A7x+3y=−25%0D%0A7%0D%0A%0D%0A+%0D%0A3%0D%0A%0D%0A=%0D%0A−%0D%0A25%0D%0A%0D%0A−7x+9y=−47%0D%0A−%0D%0A7%0D%0A%0D%0A+%0D%0A9%0D%0A%0D%0A=%0D%0A−%0D%0A47%0D%0A(1 point)%0D%0A(,
1 answer